Neglected witnesses : the fate of Jewish ceremonial objects during the Second World War and after - Bergman, Eleonora (Institute of Art and Law [u.a.], 2011)
Introduction Julie-Marthe Cohen and Felicitas Heimann-Jelinek -- "A brand plucked out of the fire" : the distribution of heirless Jewish cultural property by Jewish Cultural Reconstruction, Inc., 1947-1952 Dana Herman -- Fragments of remembrance : Viennese Judaica collections and more Felicitas Heimann-Jelinek -- The Judaica collection of Frankfurt's Museum Jüdischer Altertümer and its worldwide dispersion after 1945 Katharina Rauschenberger -- Jewish museums in the former Czechoslovakia Magda Veselská -- The history of Judaica and Judaica collections in Poland before, during and after the Second World War : an overview Nawojka Cieślińska-Lobkowicz -- The Jewish Historical Institute : history of its building and collections Eleonora Bergman -- Theft and restitution of Judaica in the Netherlands during and after the Second World War Julie-Marthe Cohen -- Italy's attitude towards Jewish cultural property during and after the Second World War Paola Bertilotti -- The fate of Judaica in Hungary during the Nazi and Soviet occupations Zsuzsanna Toronyi -- The Skirball Museum JCR Research Project : records and recollections Grace Cohen Grossman -- Appendix 1 : Washington conference principles on Nazi-confiscated art -- Appendix 2 : Declaration of the Vilnius International Forum on Holocaust-era looted cultural assets -- Appendix 3 : Resolution of the Association of European Jewish museums -- Appendix 4 : Holocaust era assets conference, Czech Republic, experts' conclusions -- Appendix 5 : Terezin Declaration on Holocaust era assets and related issues